Etika Konsumsi dalam Perspektif Iman Kristen: Studi Kasus Praktik Fast Fashion oleh Ibu-ibu KWKI di KGPM Sidang Elim Tuminting - Jhonderic Molle; Merianti Atakameng; Mario Marchellino Benyamin (PT. Giat Konseling Nusantara, 2026)
The phenomenon of fast fashion has become a global challenge with widespread impacts on the environment and social ethics, including within church communities. This study aims to analyze the clothing consumption behavior of women in the KWKI group at KGPM Sidang Elim Tuminting, and to evaluate how the church can respond to the fast fashion trend from a Christian theological perspective. Using a descriptive qualitative approach through focus group discussions and participatory observation, the findings reveal that although many members have high consumption habits, they are open to transformation when spiritual values such as simplicity, love, and ecological responsibility are emphasized. The clothing collection and redistribution activity initiated by KWKI represents a tangible expression of faith working through love. This research highlights the strategic role of the church in shaping a responsible and sustainable spirituality of consumption.